Comparative Evaluation of Physicochemical Properties of Surface Water Treated by Alum and Pawpaw Seed Powder - O. M. Ojo (Journal of Applied Sciences and Environmental Management)
Surface water treatment is crucial for maintaining water quality and safeguarding public health. Traditional methods like alum treatment have been widely used, but they often come with high costs and environmental concerns. In contrast, natural alternatives such as pawpaw seed powder offer a potentially low-cost and eco-friendly solution. Hence, the objective of this paper is to comparatively evaluate the physicochemical properties of surface water treated by using alum and pawpaw seed powder using appropriate standard methods. Initial water quality parameters included turbidity of 27 NTU, pH of 7.9, total suspended solids (TSS) of 126.8 mg/L, total dissolved solids (TDS) of 267.2 mg/L, and hardness of 321 mg/L. Post-treatment with alum reduced these values to 9 NTU, pH 7.5, TSS 50 mg/L, TDS 135 mg/L, and hardness 95 mg/L. Pawpaw seed powder treatment resulted in reductions to 6 NTU, pH 7.6, TSS 60 mg/L, TDS 160 mg/L, and hardness 130 mg/L. The findings showed significant improvement in water clarity and quality for both treatments, with pawpaw seed powder demonstrating slightly superior turbidity reduction. Cost analysis revealed that alum treatment cost a total of 9000 NGN, whereas pawpaw seed powder treatment cost 5500 NGN, primarily due to lower procurement and transportation costs. The results suggest that pawpaw seed powder is a more cost-effective and sustainable alternative to alum since it was capable of achieving comparable water quality improvements.